THE ROLE OF INTERACTIVE SKILLS IN TEACHING FOREIGN LANGUAGES - Nilufar Sayfutdinova Soyibjonovna (American Journals, 2023)
This article provides information on the use of interactive techniques and manuals in English science lessons and its wide application among students
Keywords: education, skills, productive activities, didactic goals, method, organization, approach